Biological sex impacts COVID-19 outcomes. - Sabra L Klein; Santosh Dhakal; Rebecca L Ursin; Sharvari Deshpande; Kathryn Sandberg; Franck Mauvais-Jarvis (PLoS Pathogens)
The current novel coronavirus disease 2019 (COVID-19) pandemic is revealing profound differences between men and women in disease outcomes worldwide. In the United States, there has been inconsistent reporting and analyses of male-female differences in COVID-19 cases, hospitalizations, and deaths. We seek to raise awareness about the male-biased severe outcomes from COVID-19, highlighting the mechanistic differences including in the expression and activity of angiotensin-converting enzyme 2 (ACE2) as well as in antiviral immunity. We also highlight how sex differences in comorbidities, which can be associated with both age and race, impact male-biased outcomes from COVID-19.